Film Museum Practice and Film Historiography - Lameris, Bregt; Project Muse. (Amsterdam University Press, 2017)
Rich in detail, this is a study of the interrelationships between film historical discourse and archival practices. Exploring the history of several important collections from the EYE Film Museum in Amsterdam, Bregt Lameris shows how archival films and collections always carry the historical traces of selection policies, restoration philosophies, and exhibition strategies. The result is a compelling argument that film archives can never be viewed simply as innocent or neutral sources of film history.
Includes bibliographical references (pages 245-260) and index.
Description based on print version record.
Keywords: EYE Film Instituut Nederland -- History; Nederlands Filmmuseum -- History; Motion pictures -- Historiography; Film archives -- Netherlands -- Amsterdam -- History -- 20th century; Electronic books